2017
DOI: 10.1111/1365-2656.12781
|View full text |Cite|
|
Sign up to set email alerts
|

Social behaviour and gut microbiota in red‐bellied lemurs (Eulemur rubriventer): In search of the role of immunity in the evolution of sociality

Abstract: Vertebrate gut microbiota form a key component of immunity and a dynamic link between an individual and the ecosystem. Microbiota might play a role in social systems as well, because microbes are transmitted during social contact and can affect host behaviour. Combining methods from behavioural and molecular research, we describe the relationship between social dynamics and gut microbiota of a group-living cooperative species of primate, the red-bellied lemur (Eulemur rubriventer). Specifically, we ask whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
75
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(93 citation statements)
references
References 101 publications
5
75
0
Order By: Relevance
“…Other studies have focused on closely related mammal species and generally found that host species and their gut microbes exhibit concordant relationships [8,[15][16][17][18], with the gut microbial communities of different host species forming distinct clusters [18][19][20]. Within single host species, some studies of humans and other primates have suggested that social contact patterns are the primary predictor of gut microbiome composition [21][22][23][24][25], whereas others have found that host genetics exerts a strong influence [26,27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have focused on closely related mammal species and generally found that host species and their gut microbes exhibit concordant relationships [8,[15][16][17][18], with the gut microbial communities of different host species forming distinct clusters [18][19][20]. Within single host species, some studies of humans and other primates have suggested that social contact patterns are the primary predictor of gut microbiome composition [21][22][23][24][25], whereas others have found that host genetics exerts a strong influence [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…All non-flying mammals of Madagascar belong to either one of four endemic orderslemurs, tenrecs, carnivorans, or rodents-or are recent human introductions-African bush pigs [37], cattle, cats, or dogs [38]. Recent studies have shown that the gut microbiomes of wild lemurs reflect social group membership and seasonal changes in diet [24,25,39,40], but none yet have considered the microbiomes of co-occurring mammalian species.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have focused on closely related mammal species, and generally found that host species and their gut microbes exhibit concordant phylogenies (8,1518), with the gut microbiomes of different host species forming distinct clusters (1820). Within single host species, some studies of humans and other primates have suggested that social contact patterns are the primary predictor of gut microbiome composition (2125), whereas others have found that host genetics exert a strong influence (26,27).…”
Section: Introductionmentioning
confidence: 99%
“…All non-flying mammals fall into either one of four endemic orders—lemurs, tenrecs, carnivorans, or rodents—or are recent human introductions—African bush pigs (38), cattle, cats, or dogs (39). Recent studies have shown that social contacts and diet influence the gut microbiomes of wild lemurs (24,25,40), but none have yet considered the microbiomes of co-occurring mammalian species.…”
Section: Introductionmentioning
confidence: 99%
“…Grieneisen et al, 2017) and lemurs (Eulemur rubriventer:Raulo et al, 2017). Gut microbiomes are 70 also more similar among socially connected than disconnected siblings and married couples (Dill-71McFarland et al, 2019).…”
mentioning
confidence: 99%